RIGHTS AND PROTECTION OF WIVES OVER JOINT PROPERTY UNDER POLYGAMY IN INDONESIA - Marryana, Suci; Hendro Tri Widodo, Gatut; Rattanapun, Supot (Penerbit Lafadz Jaya, 2024)
This research aims to analyse the legal protection of the first wife's rights in the division of joint property in polygamous marriages in Indonesia. Through a normative juridical approach, this research examines the legal provisions governing the division of joint property as well as the challenges in practice. The results show that despite clear arrangements in the Marriage Law and the Compilation of Islamic Law, in practice injustice often occurs to the first wife, both from formal legal aspects and socio-psychological factors. Therefore, legal policy reform and strengthening of legal protection mechanisms are needed to ensure justice for the first wife in the division of joint property in polygamous marriages.